Postoperative interventions for preventing bladder dysfunction after radical hysterectomy in women with early‐stage cervical cancer - Aue‐aungkul, Apiwat (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effectiveness and safety of postoperative interventions for preventing bladder dysfunction following radical hysterectomy in women with early‐stage cervical cancer (FIGO stage IA2 to IIA).